2020
DOI: 10.1161/atvbaha.119.313877
|View full text |Cite
|
Sign up to set email alerts
|

VLDL (Very-Low-Density Lipoprotein)-Apo E (Apolipoprotein E) May Influence Lp(a) (Lipoprotein [a]) Synthesis or Assembly

Abstract: To clarify the association between PCSK9 (proprotein convertase subtilisin/kexin type 9) and Lp(a) (Lipoprotein [a]), we studied Lp(a) kinetics in patients with loss-of-function and gain-of-function PCSK9 mutations and in patients in whom extended-release niacin reduced Lp(a) and PCSK9 concentrations.APPROACH AND RESULTS: Six healthy controls, 9 heterozygous patients with familial hypercholesterolemia (5 with low-density lipoprotein receptor [LDLR] mutations and 4 with PCSK9 gain-of-function mutations) and 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Classical knowledge is that LDL does not have apoE, nevertheless, since apoE binds to lipids through its C-terminal domain it seems difficult that it binds to HDL, VLDL, IDL and Lp(a) but not LDL at all. Indeed, lipoproteins isolated by flotation sequential ultracentrifugation showed that apoE represents 0.40%, 0.10% and 0.38% of the total mass of VLDL, LDL and HDL, respectively [2], and is found in HDL (61 ± 27%), VLDL (35 ± 25%), Lp(a) (4 ± 9%) and LDL (1 ± 1%) in fasting plasma [3]. Lipoproteins isolated by anti-apoE immunoaffinity chromatography showed the presence of 21, 19, and 5 molecules of apoE in a portion of VLDL, HDL, and LDL respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Classical knowledge is that LDL does not have apoE, nevertheless, since apoE binds to lipids through its C-terminal domain it seems difficult that it binds to HDL, VLDL, IDL and Lp(a) but not LDL at all. Indeed, lipoproteins isolated by flotation sequential ultracentrifugation showed that apoE represents 0.40%, 0.10% and 0.38% of the total mass of VLDL, LDL and HDL, respectively [2], and is found in HDL (61 ± 27%), VLDL (35 ± 25%), Lp(a) (4 ± 9%) and LDL (1 ± 1%) in fasting plasma [3]. Lipoproteins isolated by anti-apoE immunoaffinity chromatography showed the presence of 21, 19, and 5 molecules of apoE in a portion of VLDL, HDL, and LDL respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…They range from a key role of the LDLR in Lp(a) catabolism to a reduced Lp(a) synthesis. Recently, a further mechanism has been hypothesized, i.e., Very-Low-Density Lipoprotein (VLDL)–apoE production could influence Lp(a) production and/or assembly [ 69 ]. Epidemiological studies have shown differences in plasma Lp(a) concentrations between apoE genotypes based on the three major E isoforms (ε2/ε3/ε4) [ 70 ].…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 99%
“…The median Lp(a) in this study of 20.8 mg/dL seems to be higher than reported in previous studies on Japanese FH patients (12.1 mg/dL) and Japanese healthy The values are expressed according to Lp(a) categories at baseline in heterozygous FH patients under medical treatment. 25) , although exact mechanisms explaining the relationship remain to be uncovered.…”
Section: Serum Lp(a) Levels In Japanese Fhmentioning
confidence: 99%